Efficacy of perioperative immunonutrition in visceral surgery: an umbrella review protocol - Charles-Hervé Vacheron; Karem Slim; Flora Badon; Chadli Dziri; Thomas Marquillier (BMJ Open)
Introduction Immunonutrition (IN) is generally used before major visceral surgery with the intent to reduce postoperative complications, especially infectious ones. However, the conclusions of published meta-analyses are conflicting. The purpose of this review is to synthesise the data of published systematic reviews on the effectiveness of IN.Methods and analysis This protocol follows the Preferred Reporting Items for Systematic Reviews and Meta-analyses Protocols guidelines. This is an umbrella review of systematic reviews comparing IN (delivered orally 5–7 days preoperatively) with normal diet or isocaloric isonitrogenous feeding before visceral surgery performed on any of several viscera (colorectum, stomach, pancreas, liver, oesophagus). We search the systematic reviews included in the main bibliographic databases. To assess the efficacy of IN, several outcomes will be considered: the main outcome is infectious complications (surgical site infections, pulmonary infections or urinary infections) and secondary outcomes are overall morbidity, hospital length of stay and mortality. Identified reviews will be screened by two independent assessors. The methodological quality of relevant included reviews will be assessed using A MeaSurement Tool to Assess systematic Reviews (AMSTAR) instrument. The data extracted from included reviews will be synthesised using the r-Metafor package considering separate groups according to the viscus of interest. Publication bias will be evaluated, and subgroup analyses will be performed according to the quality of studies and preoperative nutritional status.Ethics and dissemination An umbrella review based on published data from systematic reviews needs no ethical approval. Furthermore, no patient will be involved in the review. Once terminated, the review will be submitted for publication in an open access journal to ensure wide dissemination of the findings.PROSPERO registration number CRD42021255177.